2004
DOI: 10.3233/nre-2004-19306
|View full text |Cite
|
Sign up to set email alerts
|

The potential of electronic organizers as a tool in the cognitive rehabilitation of young people

Abstract: Youths who have traumatic brain injury (TBI) or mental retardation and other developmental disabilities often experience cognitive challenges in using memory and organization for learning, managing daily routines, or conducting social interactions. This article presents the results of a survey of 53 youth-parent-teacher triads probing their views regarding the youth's relationship with technology. Since the sample is small, results should be viewed with caution, yet keeping in mind the study presents some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Compensatory intervention to support orientation to time includes the use of activity schedules, which is an established method to support children with autism (Koyama & Wang, ). In addition, the use of adapted calendars and other visual aids can promote orientation to time of the day, week or year (Gillette & DePompei, ). There is evidence for the effectiveness of assistive devices that compensate for a lack of time management in adults with developmental disabilities (e.g., IDs) (Arvidsson & Jonsson; Gillespie, Best & O'Neill, ; Granlund, Bond, Lindstöm & Wennberg, ; Wennberg & Kjellberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory intervention to support orientation to time includes the use of activity schedules, which is an established method to support children with autism (Koyama & Wang, ). In addition, the use of adapted calendars and other visual aids can promote orientation to time of the day, week or year (Gillette & DePompei, ). There is evidence for the effectiveness of assistive devices that compensate for a lack of time management in adults with developmental disabilities (e.g., IDs) (Arvidsson & Jonsson; Gillespie, Best & O'Neill, ; Granlund, Bond, Lindstöm & Wennberg, ; Wennberg & Kjellberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…External supports such as pagers providing reminders (van't Hooft et al, 2007;Wilson & Moffat, 1992;Wilson, Emslie, Quirk, Evans, & Watson, 2005) and electronic organisers (DePompei et al, 2008;Gillette & DePompei, 2004) may help children to achieve better functional memory. Lower-tech supports are suggested by Rankin and Hood (2005), such as visual timetables and stickers to highlight important environmental elements.…”
Section: External Cognitive Supportsmentioning
confidence: 99%
“…Little systematic research is available on school-aged individuals with disabilities and the use of generic, handheld technologies. In a 2001 survey of 53 students with disabilities, 7 to 22 years old, only 6 reported ever using an electronic organizer and only 2 reported having used an electronic organizer for keeping track of appointments (Gillette & DePompei, 2004). In the same study, students, parents, and teachers reported their perception of how the student kept track of appointments.…”
Section: Memory and Organizational Deficits And The Use Of External Mmentioning
confidence: 99%
“…Children reported exposure to many more types of devices and had increased familiarity with computer operations. However, they were using the devices for enjoyment rather than for completion of daily tasks (Gillette & DePompei, 2004). As a result of these surveys and additional focus groups, the second stage of research moved to in vivo trials of PDAs with these populations.…”
mentioning
confidence: 99%